Performance evaluation of RegCM5 in long-term convection-permitting simulations for high-urbanized areas in Vietnam - Nguyen-Xuan, Thanh; Nguyen-Le, Dzung; Ngo-Duc, Thanh (Vietnam Journal of Earth Sciences, 2025)
This study is the first in Vietnam to assess the impact of urbanization on the local climate in Hanoi and Ho Chi Minh City using the Regional Climate Model version 5 (RegCM5) at convection-permitting (CP) resolution. Simulations were conducted at a horizontal grid spacing of 2 km, driven by the fifth-generation global reanalysis produced by the European Centre for Medium-Range Weather Forecasts (ERA5), and incorporating annually updated urban information from 2000 to 2020. Unlike previous studies that relied on coarse-resolution simulations and static urban data, the latest version of RegCM5 enables stable long-term simulations with significantly reduced computational demands. The results yield three key findings. First, the 2 km simulations outperform those at 10 km resolution, highlighting the advantages of CP-scale modeling. In specific cases, the 2 km simulations even surpass the performance of the Vietnam Gridded Climate (VnGC) dataset when validated against station observations. Second, incorporating updated urban information allows the model to more accurately capture the temporal evolution of urbanization impacts, particularly evident from late afternoon (around 16:00 local solar time, LST) to midnight (around 01:00 LST). Third, the study finds that the urban heat island (UHI) effect in both cities is stronger during this late afternoon to midnight period and intensifies with increasing background temperatures. The UHI magnitude in Hanoi is generally greater than in Ho Chi Minh City.